On Sphallambyx mexicanum and key to species of Sphallambyx (Coleoptera, Cerambycidae, Cerambycinae) - Santos-Silva, Antonio; Botero, Juan Pablo; Galileo, Maria Helena M. (Zootaxa, 2018)
The male of Sphallambyx mexicanum Galileo & Martins, 2007 is described for the first time; the geographical distribution of the species is expanded to Guatemala, Costa Rica, and Panama. Sphallambyx chabrillacii (Thomson, 1857) is formally excluded from the fauna of Costa Rica. A key to species of Sphallambyx Fragoso, 1982 is provided.